Common Cold – an Umbrella Term for Acute Infections of Nose, Throat, Larynx and Bronchi - Kardos, P.; Malek, F. A. (Pneumologie, 2017)
Acute respiratory tract infections, i. e. rhinitis, sinusitis, pharyngitis, laryngitis, bronchitis, belong to the most common medical conditions with a high economic burden. Nonetheless, there is little agreement concerning their differential diagnosis.This paper will discuss to what extent different anatomical sites of acute respiratory tract infections can be uniquely identified or whether the overlap and consecutive development in signs and symptoms renders these distinctions meaningless.Acute respiratory tract infections are variable but definition of diagnostic categories based on the anatomical sites of the dominant complaints shows that signs and symptoms both overlap to a great extent and/or emerge successively. Thus, in common cold distinguishing between acute symptom-based diagnoses arising from different anatomical sites of the aerodigestive system remains elusive. Therefore, preferred symptomatic treatments should foster a resolution of all possible symptoms as opposed to an isolated treatment of a single symptom (e. g. mucus hypersecretion) according to the presumed anatomical site (i. e. acute bronchitis).